2020
DOI: 10.1002/adma.201908385
|View full text |Cite
|
Sign up to set email alerts
|

Trace‐Level, Multi‐Gas Detection for Food Quality Assessment Based on Decorated Silicon Transistor Arrays

Abstract: and mass-sensitive sensors, [9] but few of these have been demonstrated to be cost, power, and size effective. For instance, the widely commercialized resistance-based metal oxide sensors must typically be operated at high temperatures to enable the adsorption interactions required for transduction. [8,[10][11][12] This results in higher power consumption as operation temperatures must be adjusted by a built-in heater. While other efforts have focused on the optimization of sensing materials [4,13,14] and sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
86
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(96 citation statements)
references
References 42 publications
1
86
0
Order By: Relevance
“…An automated control of food freshness by gas sensors requires resistivity to humidity and sensitivity towards volatile thiol-containing compounds, which are related to proteins decomposition at 100 ppb range 5 , 7 , 59 . Fast, sensitive and reusable sensors are long awaited in food industry to replace long and expensive bacteriological methods 4 , 60 .…”
Section: Introductionmentioning
confidence: 99%
“…An automated control of food freshness by gas sensors requires resistivity to humidity and sensitivity towards volatile thiol-containing compounds, which are related to proteins decomposition at 100 ppb range 5 , 7 , 59 . Fast, sensitive and reusable sensors are long awaited in food industry to replace long and expensive bacteriological methods 4 , 60 .…”
Section: Introductionmentioning
confidence: 99%
“…An interesting class of devices that have been developed for very selective gas concentration detection in the headspace of food packaging are silicon-based optical transducers composed of optical circuits integrated in silicon semiconductor material [235].…”
Section: Optical-based Sensorsmentioning
confidence: 99%
“…Common markers for gas‐targeting food sensors include carbon dioxide, [ 31,43 ] oxygen, [ 44–48 ] volatile organic compounds (VOCs), [ 49–52 ] and biogenic amines (BAs). [ 21,53–56 ]…”
Section: Food Sensorsmentioning
confidence: 99%
“…Yuan et al recently presented a low cost multiplex gas detection system that monitors ammonia, hydrogen sulfide, and humidity to track food decomposition. [21] The devices employ silicon-based chemically-sensitive field effect transistors that are decorated with sensing materials (ruthenium, silver, and silicon oxide) that produce sensitive and selective electronic responses to the targeted gases. The sensors are combined with a custom printed silicon-based circuit board to construct a portable device and the authors demonstrated the efficacy of the sensor by tracking the spoilage of pork belly.…”
Section: Figure 2 A)mentioning
confidence: 99%
See 1 more Smart Citation